2001
DOI: 10.1247/csf.26.95
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Cells Provide Signals Different from Cytokines for STAT5 Activation in Hematopoietic Cells.

Abstract: ABSTRACT. After detachment from the stromal cells, hematopoietic stem cells are thought to differentiate to the cytokine-dependent stages where their growth and differentiation are promoted by these cytokines. To examine the stromal regulation of hematopoietic stem cells, we previously established a primitive hematopoietic stem-like cell line, THS119, whose growth was dependent on the bone marrow stromal cell line, TBR59, and from which IL-3-(THS119/IL-3) or IL-7-(THS119/IL-7) dependent cell lines were then ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…It is noteworthy that STAT5 is one of the transcription factors responsive to IL-7 (51)(52)(53)(54)(55)(56)(57). In this report, in addition to confirming the diabetessuppressive properties of iDCs as we have previously published (25), we demonstrate that, at least in the NOD mouse, treatment of NOD-derived T-cells with IL-7 in vitro results in an increase in the steady-state numbers of CD4 ϩ…”
Section: Cd25supporting
confidence: 85%
“…It is noteworthy that STAT5 is one of the transcription factors responsive to IL-7 (51)(52)(53)(54)(55)(56)(57). In this report, in addition to confirming the diabetessuppressive properties of iDCs as we have previously published (25), we demonstrate that, at least in the NOD mouse, treatment of NOD-derived T-cells with IL-7 in vitro results in an increase in the steady-state numbers of CD4 ϩ…”
Section: Cd25supporting
confidence: 85%
“…Interestingly, we found that STAT5 could bind near the MCL1 gene, albeit without leading to its transcriptional activation (supplemental Figure 4), which is in agreement with the fact that IL-7 does not upregulate Mcl-1 protein in these cells (supplemental Figure 6). Genes upregulated by IL-7 in a STAT5-dependent manner in TAIL7 cells include HRH2, APOL4, and CA6, as well as, expectedly, OSM, IKZF4, PIM1, SOCS2, and CISH, [45][46][47][48][49] whereas among the top downregulated genes, we found BCL6, NLRP6, and IL10 ( Figure 5D; supplemental Figure 4). We validated these results by qPCR analysis of IL-7-treated TAIL7 cells in the presence or absence of S5i.…”
Section: Il-7-stimulated Stat5-dependent Transcriptional Network Anamentioning
confidence: 80%
“…IL-7Ra is expressed from the early pro-B through the early pre-B stage of B-cell development and may be a marker for the common lymphoid progenitor (11,28). Signal transduction through both IL-7R and TSLPR complexes ultimately results in the activation of signal transducer and activator of transcription (STAT) 5 and subsequent cell proliferation, but does so through different pathway intermediates: IL-7 signals through the Janus-activated kinase 1/3 (JAK1/3) kinases, whereas the TSLP-mediated signaling intermediates before STAT5 activation have not been fully elucidated (29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%